A VSi2P4/FeCl2 van der Waals heterostructure: a two-dimensional reconfigurable magnetic diode. Issue 33 (10th August 2022) - Han, Jiangchao; Feng, Yulin; Gao, Guoying
Abstract : The spin-dependent transmission path in the VSi2 P4 /FeCl2 heterostructure. Abstract : Reconfigurable magnetic tunnel diodes have recently been proposed as a promising approach to decrease the base collector leakage currents. However, conventional bulk interfaces usually suffer from strong Fermi level pinning, making it difficult to miniaturize spintronic devices. Fortunately, 2D van der Waals (vdW) systems with ultra-clean interfaces and without dangling bonds can solve this problem. Inspired by the recently discovered novel electronic states of type-II spin gapless semiconductor in 2D VSi2 P4 and half-metal in 2D FeCl2, we propose the VSi2 P4 /FeCl2 vdW heterostructure, and investigate the interface Schottky barrier and the bias-voltage-dependent spin transport properties by using density functional theory and the nonequilibrium Green's function. The most stable vdW interface is determined from the possible twelve interfaces with different stacking sequences and rotation angles. The interface Schottky barrier is beneficial to electrons moving in the spin-down channel due to the Ohmic contact. The heterostructure exhibits a huge rectification ratio (up to 2.9 × 10 5 %) and an excellent spin filtering effect with zero threshold bias voltage, which are explained in terms of the spin-dependent band structure, transmission spectrum and transmission path. These results indicate the promising applications of the VSi2 P4 /FeCl2 vdW heterostructure as a 2D reconfigurable magnetic diode and a spin filter with miniaturization and low energy consumption.